Tratamento da leishmaniose cutanea difusa (LCD) com a associacao antimoniato-N-metilglucamina (Glucantime®) e sulfato de paramomicina (Gabbrox®) - Costa, Jackson Maurício L.; Mendes, Sandra; Melo, Luciana S.; Figueredo, Ivan; Rebêlo, José Manuel M. [UNESP]; Saldanha, Ana Cristina R.; Alves Gama, Mônica Elinor; Barral, Aldina (My University, 1999)
Diffuse cutaneous leishmaniasis (DCL) is a rare form of tegumentary leishmaniasis (TL) and 350 cases have been reported world wide. Presently in Brazil, there were 31 cases reported corresponding to 8.9% of the world cases. The state of Maranhao contributed with ten cases (32.3%) of national reports. Recently the authors had opportunity to follow two new cases of DCL, both from the countryside of that state totaling 12 cases. The parasite Leishmania L. amazonensis was incriminated in the disease, confirming the available data as being the unique species to produce DCL in this state. The therapy associating meglumine anthimoniate with paramomicine sulphate (Gabbrox®) during 90 days, showed good tolerance and favorable response, being another option for fills form of DCL that constituted a challenge to science so far.
Treatment of diffuse cutaneous leishmaniasis (DCL) with meglumine anthiomoniate (Gluncantime)® associated with paramomicine sulphate (Gabbrox)®
Keywords: Brazil; Cutaneous; Leishmaniasis; meglumine antimonate; paromomycin; adolescent; case report; female; human; leishmania; skin leishmaniasis